The Effects Of Transformational Leadership Style On Employee Performance With Organizational Culture As Mediating Variable In BPJS Kesehatan Pontianak - KHAIR, DARUL KHAIR B12112022 (Jurnal Manajemen Update, 2018)
This study aims to assess the performance of Pontianak Health BPJS employees by using transformational leadership style variables as independent variables and organizational culture as mediating variables. Data collection method using questionnaires which are distributed to 53 respondents, using census sampling techniques and Likert scales is used for data measurement. The Classical Assumption Test and path analysis were used to process the data using the IBM SPSS v22 application. The results of this study indicate that transformational leadership style has a positive and significant effect on employee performance, transformational leadership style has a positive and significant relationship with organizational culture, and organizational culture has a positive but not significant impact on employee performance.Keywords : Transformational Leadership Style, Organizational Culture, Employee Performance, BPJS Keesehatan PontianakÂ DAFTAR PUSTAKAAbbasi, E., Akbari, M., Tajeddini, K. (2015). Organizational Learning Capabilities: Evidence from the Iranian Agricultural Higher Education System. Iranian Journal of Management Studies (IJMS) Vol. 8, No. 1. pp: 117-138 ISSN: 2345-3745Allen, P., Bennett, K., Heritage, B. (2014). SPSS Statistics Version 22: A Practical Guide. Cengage Learning Emea.Avolio, B. J.,Â  Bass, Â B. M. (2004). Multifactor Leadership Questionnaire: Third Edition Manual and Sampler Set. Mind Garden Inc., Palo Alto, CA.Bass, B. M. (1985). Leadership and Performance Beyond Expectation. New York: Free Press.Bass, B. M. (1997). â€œDoes the transactional-transformational leadership paradigm transcend organisational and national boundariesâ€, American Psychologist, Vol. 52 No.2Bass, B. M., Avolio, B. J. (1993). Transformational Leadership and Organizational Culture. Public Administration Quarterly.Belias, D., Koustelios, A. (2014). The Impact of Leadership and Change Management Strategy on Organizational Culture in Trikala, Greece. European Scientific Journal, Edition Vol. 10, No. 7Brown, A. (1998). Organizational culture. Singapore: Prentice Hall.Bruce T. J. et al. (1995). How Transformational Leaders Lead In The Hospitality Industry. Internal Journal of Hospitality Management.Bukhari, S. J. A. et al. (2014). Leadership Style and Employees Performance: Evidence from Banking Sector of Pakistan. Journal of Education and Literature. Vol. 2Chen, J. C. (2003). The Leadership Styles of The Person in Charge and The Organizational Culture to The Influence of Military Institute Personnel Commitment Behavior-The Case of Military Institute, Taiwan. Institute of Management Science, Ming Chuan University.Chen, L. Y., Barnes, F. B. (2006). Leadership Behaviors and Knowledge Sharing Inprofessional Service Firms Engaged In Strategic Alliances. Journal of Applied Management and Entrepreneurship.Creswell, J. W. (2008). Research Design Qualitative, Quantitative, and Mixed Methods Approaches. Third Edition. SAGE Publications, Inc.Deal, T., Kennedy, A. (1982). Corporate Culture: The Rites and Rituals of Corporate Life, Reading. Massachusetts: Addison-Wesley Publishing Company, Inc.Denison,Â  D. R. (1984). Bringing Corporate Culture to The Bottom Line. Organizational Dynamics.Dessler, G. (1992). Manajemen Personalia. Jakarta: Erlangga.Dubrin, A. J. (2001). Leadership-Research Finding, Practices, and Skills. 3rd Edition, Houghton Mifflin Company Boston New York.Eran, V. G. (2007). Leadership Style, Organizational Politics and Employeesâ€™ Performance: An Empirical Examination of Two Competing Models. Personnel Review.Fauzi, A. (2017). Ekonomi.kompas.com Retrieved from : http://ekonomi.kompas.com/read/2017/09/25/172838526/defisit-bpjs-kesehatan-diperkirakan-capai-rp-9-triliun-tahun-iniGibson et al. (1995) in Pariaribo, N. (2014). Pengaruh Gaya Kepemimpinan dan Motivasi Kerja Terhadap Kepuasan Kerja Serta Dampaknya Terhadap Kinerja Pegawai Pada Badan Perencanaan Pembangunan Daerah Di Kabupaten Supiori. S2 Thesis, Universitas Atma Jaya Yogyakarta.Giritli, H., Oraz, G. T. (2003). Leadership Styles: Some Evidence from the Turkish Construction Industry. â€œConstruction Management and Economicsâ€. 22(3), 253-262Golden III, J. H., Shriner, M. (2017). Examining Relationship between Transformational Leadership and Employee Creative Performance: The Moderator Effects of Organizational Culture. The Journal of Creative Behavior, Vol. 0, Iss. 0, pp. 1-14Hakim, S. (2017). Pontianak.tribunnews.com Retrieved from : http://pontianak.tribunnews.com/2017/10/24/bpjs-kesehatan-minta pelayanan-pasien-tak-dibedakanHatch, M. J. (1993, 2000) in Karacsonyi (2006). The Dynamics of Organizational Culture. Academy of Management Review 18 (4): 657â€“693Hofstede, G. (1980). Culture's consequences: international differences in work related values. Beverly Hills, CA: Sage.Imam & Muh (2017). Thetanjungpuratimes.com Retrieved From : https://thetanjungpuratimes.com/2017/08/22/bpjs-kesehatan-cabang-kota-pontianak-publis-capaian-program-jkn-kis/Ismail A. et al. (2009). The Mediating Effect of Empowerment in The Relationship Between Transformational Leadership and Service Quality. J. Bus. ManageJames, K. M. (2005).Â  A Meta-Analysis of Transformational and Transactional Leadership Correlates of Effectiveness and Satisfaction. Retrieved from http://www.ijrcm.org/articles/cm3.htJohns, G. (1998) Comportament organizaÅ£ional, Ed. EconomicÄƒ.Kandula, S. R. (2006). Performance Management. Prentice Hall of India Private LimitedKhan, I. U., Nawaz, A. (2016). Leadership Styles and The Employees Performance: A Review. Gomal University Journal of Research (GUJR) Vol 32 Issue 2.Khan, R. (2016). Leadership Style and Organization Performance. MPRA Paper No. 70387Kothari, C. R. (2004). Research Methodology Methods and Techniques. 2nd Edition. New Age International Publishers, New Delhi.Kusuma, D. R. (2015). finance.detik.com Retrieved From : https://finance.detik.com/moneter/2982958/bpjs-kesehatan-tanggung-defisit-rp-6-triliun-sampai-akhir-2015Lee, C. F. (2002). Impact of Leadership Styles on Work Involvements of Subordinates-National Taxation Bureau of Kaohsiung, Ministry of Finance, Taiwan. Graduate Institute of Business Administration, National Cheng Kung University.Magee, K. C. (2002). The Impact of Organizational Cultureon the Implementation of Performance Management. Available from Dissertations and Theses database (UMI No. 3047909)Mardiana, C. F. (2017). finance.detik.com Retrieved From : https://finance.detik.com/moneter/3509249/bpjs-kesehatan-paparkan-kinerja-2016-apa-saja-capaiannyaMasakure, O. (2016). The Effect of Employee Loyalty on Wages. Journal of Economic Psychology, 56, 274-298Mathis L. R., John, J (2006). Human Resource Management. Jakarta : Salemba Empat.Motowidlo & van Scotter (1994) in Andreia (2012). The Perceived Leadership Style and Employee Performance in Hotel Industry â€“ a Dual Approach. West University of Timisoara.Nelson, D. L., Quick, J. C. (2011). Understanding Organizational Behaviour. Belmont: Cengage southwestern.Omukaga, A., A. (2016). Effects of Organizational Culture on Employee Performance At AON Limited, Nairobi, Kenya. School of Business, University of Nairobi.Pattanayak, B. (2005). Human Resource Management. Prentice Hall of India Pvt. Ltd; 3rd Edition.Rivai, V. (2009). Manajemen Sumber Daya Manusia Untuk Perusahaan. Dari Teori ke Praktik. Jakarta: Raja Grafindo Persada.Rizwan, M., Nazar, K., Nadeem, B., & Abbas, Q. (2016). The Impact of Workforce Diversity towards Employee Performance. American Journal of Marketing Research.Robbins, S. P. (1998). Organization Behavior, Concepts, Controversies, Application. 7th Edition, Englewood Cliffs and PT. Prenhallindo, Jakarta.Robbins, S. P. (2003). Organizational Behaviour, Tenth Edition. Jakarta : Salemba Empat.Robbins, S. P. (2001). Organizational Behavior: Concepts, Controversies, and Applications. 8th ed, NY : Prentice Hall Inc.Robbins, S. P. (2008). Perilaku organisasi. Jakarta : PT. Indeks Kelompok GRAMEDIA.Robbins, S. P., Judge, T. (2007). Organizational behavior. Pearson Prentice Hall.Roflin, E. (2009). Using Trimming Method on Path Analysis. Journal of Research Science Special Edition 09:12-01Schein, E. (1995). Organizational culture. Frankfurt: Campus Verlug.Shelley, D. D., Francis, J. Y., Leanne, E. A., William, D. S. (2004). Transformational Leadership and Team Performance. Journal of Organizational Change Management, Vol. 17Shurbagi, A. M. A., Zahari, I. B. (2013). The Relationship between Transformational Leadership and Organizational Culture in National Oil Corporation of Libya. International Journal of Business Administration. Vol. 4Trice, H. M., Beyer, J. M. (1991). Cultural Leadership in Organizations. Organization Science 2 (2):149â€“169Uddin, M. J., Luva, R. H., Hossian, S., M., M. (2013). Impact of Organizational Culture on Employee Performance and Productivity : A Case Study of Telecommunication Sector in Bangladesh. International Journal of Business & Management Vol. 8 No. 2Xenikou, A., Simosi, M. (2006). Organizational Culture and Transformational Leadership as Predictors of Business Unit Performance. Journal of Managerial Psychology Vol. 21 No. 6, 2006 pp. 566-579